Les dispositifs de gestion d’un contexte à l’autre : métissage, ruptures, innovations ? - Sarah Botton (Recherches Sociologiques et Anthropologiques, 2009)
This article looks at the management practices of two urban service enterprises, subsidiaries of the French groups Suez and EDF, who intervened in the 1990’s and after 2000 in the privatized distribution of water and electricity in Buenos Aires. The questioning involves the management arrangements that these organizations set up for the inhabitants of the downtrodden quarters, new actors in a “merchandized” service relationship, whose particularity is that they are practically insolvent, often housed informally, or in a clandestine manner, at the heart of a truly “political problem”. Thanks to question charts, notably proposed by the sociology of management, we thus ask about the tools set up by these enterprises, i.e., the dynamics of recombining, innovating or crossbreeding management arrangements “imported” from European experiences (training) and about development projects (participative types of intervention). We also investigate the emergence of a new profession of “social engineer” in a particular context of very high social polarization, as well the related analyses involving modes of legitimization and anchorage of this new profession.